Devotion in Flesh and Bone The Mummified Corpses of Mount Yudono Ascetics in Edo-Period Japan - Castiglioni, Andrea (2019)
In contemporary Japan the fame of Mount Yudono (Yamagata prefecture) derives from the high concentration of mummified bodies of ascetics, which are enshrined in various temples of this mountainous area. These taxidermic statues are often interpreted as the final result of a voluntary abandonment of the body in which the ascetic self-interred within a sepulchral underground cell before dying. However, the present article seeks to reconsider these mummies as ad hoc manipulations of the ascetics’ corpses, which were executed by disciples and lay devotees after the natural death of the ascetics. Such a rethinking of the mummified bodies of Yudono does not diminish their religious value as cultic objects; rather, it adds complexity by highlighting a creative tension between the historical and meta-historical dimension of these full-body relics. The semantic variety of such mummified bodies results from a continual oscillation between narrative sources, which, on the one hand, depict Yudono ascetics within the ordinariness of their human existence (historical dimension) and, on the other, make them transcend space and time (meta-historical dimension). The article demonstrates that the ascetics of Yudono could extend their charisma beyond the normal lifespan thanks to their mummified corpses, which worked as sensorial supports of the ascetics’ power upon which lay devotees could continuously rely.